Brillouin spectroscopy of a hybrid silicon-chalcogenide waveguide with geometrical variations - Zarifi, Atiyeh; Stiller, Birgit; Merklein, Moritz; Liu, Yang; Morrison, Blair; Casas-Bedoya, Alvaro; Ren, Guanghui; Nguyen, Thach G.; Vu, Khu; Choi, Duk-Yong; Mitchell, Arnan; Madden, Steven J.; et al. (Optics Letters, 2018)
Recent advances in design and fabrication of photonic-phononic waveguides have enabled stimulated Brillouin scattering in silicon-based platforms such as underetched silicon waveguides and hybrid waveguides. Due to the sophisticated design and, more importantly, high sensitivity of the Brillouin resonances to geometrical variations in micro- and nano-scale structures, it is necessary to have access to the localized opto-acoustic response along those waveguides to monitor their uniformity and maximize their interaction strength. In this Letter, we design and fabricate photonic-phononic waveguides with a deliberate width variation on a hybrid silicon-chalcogenide photonic chip and confirm the effect of the geometrical variation on the localized Brillouin response using a distributed Brillouin measurement.
CRIS-Team Scopus Importer:2021-06-29